Co-incidence of Human Papillomaviruses and Epstein–Barr Virus Is Associated With High to Intermediate Tumor Grade in Human Head and Neck Cancer in Syria - Gupta, Ishita; Ghabreau, Lina; Al-Thawadi, Hamda; Yasmeen, Amber; Vranic, Semir; Al Moustafa, Ala-Eddin; Malki, Mohammed I. (Frontiers in Oncology, 2020)
High-risk human papillomaviruses (high-risk HPVs) have been recently reported to be co-present with Epstein–Barr virus (EBV) in different types of human cancers including head and neck (HN), where they can cooperate in the initiation and/or progression of this cancer. Accordingly, we herein explored the prevalence of high-risk HPVs and EBV in 80 HN cancer tissues from the Syrian population using polymerase chain reaction, immunohistochemistry, and tissue microarray methodologies. We report that high-risk HPVs and EBV are present in 35/80 (43.7%) and 41/80 (51.2%) of our samples, respectively; and the most frequent HPVs types are 33, 16, 18, 45, 52, 58, 35, 51 and 31, in this order. More significantly, our data reveal that 25/80 (31.2%) of cancer cases are positive for high-risk HPVs as well as EBV and their co-presence is associated with high/intermediate grade squamous cell carcinomas. These data confirm the copresence of high-risk HPVs and EBV in HN cancers in the Syrian population of the Middle East and demonstrates that their co-incidence is linked to a more aggressive cancer phenotype. Thus, future studies are required to confirm these data and elucidate the exact role of high-risk and EBV cooperation in human HN carcinogenesis.